Scientific Libraries of Yakutia in the Pre-Revolutionary Period (1853—1917) - Tuiaara A. Androsova; Туйаара Анатольевна Андросова (Bibliotekovedenie [Russian Journal of Library Science], 2021)
The article considers the history of foundation and development of scientific libraries in Yakutia. In many ways, the opening of libraries was caused by the scientific interest in Siberia, the emergence of scientific and cultural-educational societies. Libraries strengthened the status of the societies and provided information support for their activities. The first scientific libraries were opened at the Yakut Regional Statistical Committee (1853), the Yakut Regional Museum (1891), the Yakut Department of the Agricultural Society (1899) and the Yakut Branch of the Imperial Russian Geographical Society (1913).The article notes the contribution of the State Public Scientific and Technical Library of the Siberian Branch of the Russian Academy of Sciences and the National Library of the Republic of Sakha (Yakutia) to the study of history of libraries and librarianship in Siberia, including Yakutia. Particularly, the author describes the influence of political exiles on the formation of libraries and the development of culture in the region. The author focuses on the activities of the Yakut Regional Statistical Committee, which established one of the first special libraries, which later became the main one for scientific libraries. The article considers its activities as an integral part of scientific research in the Eastern Siberia, since the Committee not only collected statistical data on the region, but also supported research institutions, took part in organizing expeditions to study the region, etc. The author describes the role of the Secretary of the Committee, S.F. Saulsky, in the ordering and systematization of the library’s collection, as well as the role of A.I. Popov, state councillor, full member of the Imperial Russian Geographical Society, in the organization of the Yakut Regional Museum. The article reveals the activities of the museum library on selection of books and periodicals of scientific societies, Sibirika, local history literature and manuals for the identification of collections and their ...